Unprecedented Reactivity of AgSCF3 with o-Isocyanobiaryls: Synthetic and Mechanistic Insight - Phetcharawetch J. (2023)
The work reports an unusual reaction of o-isocyanobiaryls and AgSCF3, which led to the unexpected formation of 6-(trifluoromethyl)phenanthridines and o-biaryl isothiocyanates as products, instead of the expected 6-((trifluoromethyl)thio)phenanthridines. Density functional theory (DFT) calculations on the relative free energy of β-fragmentation and 6-endo-trig radical cyclization pathways of the key thioimidoyl radical intermediate suggested that β-fragmentation of the S−CF3 bond is preferable, releasing CF3 radical and o-biaryl isothiocyanate. The CF3-imidoyl intermediate arising from the addition of CF3 radical to o-isocyanobiaryl then underwent 6-endo-trig radical cyclization to provide 6-(trifluoromethyl)phenanthridines. This work demonstrates the alternate application of AgSCF3 in generating trifluoromethylated and isothiocyanate products.